IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION (PAI) TEACHER PROFESSIONAL ETHICS IN THE USE OF LEARNING TECHNOLOGY AT SDN BANDARAN 3 PAMEKASAN - Qorry 'Aini Novelia; Moh. Hawaijul Asrori; Luluk Ainiyah Ramadani; Wildatun Nasihah; Abd. Mukhid (SOSIOEDUKASI, 2026)
This research aims to describe the application of professional ethics for Islamic Religious Education (PAI) teachers in the use of learning technology at SDN Bandaran 3 Pamekasan. This research identifies various types of technology used, such as digital multimedia (video, animation, PowerPoint) and social media (WhatsApp, Instagram) as teaching tools. According to research, the practice of professional ethics emerges through professional dedication in presenting educational materials, respectful digital interactions, equitable treatment in assessments, and modeling exemplary digital behavior for students.. In addition, this research highlights existing challenges, both from within and without, including a lack of ethical awareness and pressure from the surrounding environment, and offers solutions through ongoing training and the formation of communities of practice. Integrating ethics in the use of technology is very important to maintain the quality of PAI learning in the digital age.